C57BL/6J mice exposed to perfluorooctanoic acid demonstrate altered immune responses and increased seizures after Theiler’s murine encephalomyelitis virus infection - Pérez Gómez, Aracely A.; Wang, Meichen; Kochan, Kelli; Amstalden, Katia; Young, Colin R.; Welsh, C. Jane; Phillips, Timothy D.; Brinkmeyer-Langford, Candice L. (Frontiers in Immunology, 2023)
Neurological diseases can stem from environmental influences such as antecedent viral infections or exposure to potential toxicants, some of which can trigger immune responses leading to neurological symptoms. Theiler’s murine encephalomyelitis virus (TMEV) is used to model human neurological conditions associated with prior viral infections, with outcomes partly attributable to improper induction and regulation of the immune response. Perfluorooctanoic acid (PFOA) can alter pathologies known to influence neurological disease such as inflammatory responses, cytokine expression, and glial activation. Co-exposure to TMEV and PFOA was used to test the hypothesis that early life exposure to the potential immunotoxicant PFOA would affect immune responses so as to render TMEV-resistant C57BL/6J (B6) mice susceptible to viral-induced neurological disease. Neonate B6 mice were exposed to different treatments: non-infected, sham-infected with PBS, and TMEV-infected, with the drinking water of each group including either 70 ppt PFOA or filtered water. The effects of PFOA were evaluated by comparing neurological symptoms and changes in immune-related cytokine and chemokine production induced by viral infection. Immune responses of 23 cytokines and chemokines were measured before and after infection to determine the effects of PFOA exposure on immune response. Prior to infection, an imbalance between Th1, Th2, and Treg cytokines was observed in PFOA-exposed mice, suppressing IL-4 and IL-13 production. However, the balance was restored and characterized by an increase in pro-inflammatory cytokines in the non-infected group, and a decrease in IL-10 in the PFOA + TMEV group. Furthermore, the PFOA + TMEV group experienced an increase in seizure frequency and severity. Overall, these findings provide insight into the complex roles of immune responses in the pathogenesis of virus-associated neurological diseases influenced by co-exposures to viruses and immunotoxic compounds.